1984
DOI: 10.1079/bjn19840120
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium absorption in mature ewes infused intrarumenally with magnesium chloride

Abstract: 1. The effects of magnesium Supplementation on Mg absorption proximal and distal to the pylorus in ewes maintained on a grass diet were investigated using a combination of balance, digesta flow and electropotential measurements.2. Three mature ewes each received by intrarumenal infusion a supplement of 0, 1,2 and 3 g Mg/d in sequence over four 10-d periods.3. Net Mg absorption distal to the pylorus took place down its electrochemical gradient, although the quantity absorbed remained small during the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…PEG was used as a marker for estimating digesta flow. Nearly all (> 95%) of the total magnesium in the digesta of the abomasum was found to be in the liquid phase which agrees with data from the literature (McLean, Buchan & Scott, 1984;Ben-Ghedalia et al 1975). Consequently, the flow of magnesium has been evaluated from the magnesium concentration multiplied by the liquid flow rate of the abomasum.…”
Section: Flow Of Digestasupporting
confidence: 85%
“…PEG was used as a marker for estimating digesta flow. Nearly all (> 95%) of the total magnesium in the digesta of the abomasum was found to be in the liquid phase which agrees with data from the literature (McLean, Buchan & Scott, 1984;Ben-Ghedalia et al 1975). Consequently, the flow of magnesium has been evaluated from the magnesium concentration multiplied by the liquid flow rate of the abomasum.…”
Section: Flow Of Digestasupporting
confidence: 85%
“…Conversely, as more dietary Mg is absorbed in the forestomachs the concentration of Mg in colonic digesta is reduced and the quantity of Mg absorbed in the hindgut decreases. This hypothesis suggested by these model results is consistent with the experimental observations of McLean et al (1984) and Dalley et al (1997). In fact, an inspection of the model results presented in Table 8 of the current'paper compare favourably with the experimental resuits of Table 2 of Dalley et al (1997).…”
Section: Model Challengesupporting
confidence: 90%
“…The results of the model including absorption from the hindgut, with kHgPl set at 2-5, are represented in Table 8 in the same format as previously, and indicate much closer agreement between the model and the unpublished results of Dingwall and Field. That absorption occurs in the hindgut has been observed by several other workers (Tomas & Potter, 1976b;McLean et al 1984) whose data are not shown by Grace (1983).…”
Section: Model Challengementioning
confidence: 50%
See 1 more Smart Citation